PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DENGAN KEDISIPLINAN KARYAWAN SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan Bagian Produksi Dan Galvanis di PT. Kurnia Adijaya Mandiri) - MOKHAMMAD KHUKAIM BARKHOWA; Fitri Lukiastuti; Himawan Arif Sutanto (Magister Manajemen STIE Bank BPD Jateng, 2017)
The decline in performance has become a serious problem for many companies; due to the low level of performance is a measure that can be used as an indication of a fundamental problem in the company. This has led to increasingly fierce competition between companies. Leadership is an important aspect that can affect the performance of employees with employee discipline as an intervening variable. The purpose of this study was to analyze the influence of leadership on the performance of employees with employee discipline as an intervening variable. Samples from this study are as many as 132 people out of a population of 132 employees. The sampling method using Census Sampling. Analysis of data using Simple Linear Regression, Multiple Linear Regression Models and Sobel Test. The results showed leadership and discipline positive impact and significant on employee performance, leadership positive effect and significant on employee discipline and leadership positive effect and significant on employee performance through employee discipline.